THEORY OF REHABILITATION NURSING AS AN EMANCIPATORY PROCESS: NOTE PREVIEW - Caroline Porcelis Vargas; Milena Amorim Zuchetto; Soraia Dornelles Schoeller; Maria Manuela Ferreira Pereira Da Silva Martins (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Introduction: Rehabilitation nursing care has its practice outlined in the international scenario, constituting an evidence-based care that aims to add quality of life and, for that, it is necessary that nursing theories scientifically support the practice performed. It is known that many health and nursing theories make up the practical scope of assistance in this specialty, however it is time to reflect theoretically what we can do differently. Objectives: To build a theoretical model about rehabilitation nursing as an emancipatory process, as well as to internally validate the content and apply it as a theory in the reality of rehabilitation. Method: Methodological study of theory construction in nursing. Results: It is expected to build a Rehabilitation Nursing Theory in the light of Axel Honneth's Theory of Recognition, through an orthodontic methodological flow and literary foundation and practical experience. Conclusion: Further studies are needed to deepen rehabilitation nursing care as a science. That said, the present study proposes the construction of a Rehabilitation Nursing Theory.